O AJUSTE FISCAL DO GOVERNO FEDERAL ENTRE 1999 e 2001 - José Lúcio Alves Silveira (Universidade Federal do Maranhão, 2010)
This study demonstrates that the non-financial expenditure of the federal government wasnt excessive in the late 1990s. Additionally, we hi9hli9ht the 9rowth 01 real interest payments, which became the main variable 01 the operational delicits between 1999 and 2001.